PENGARUH MODEL STUDENT FACILITATOR AND EXPLAINING BERBASIS REINFORCEMENT TERHADAP PENGUASAAN KOMPETENSI PENGETAHUAN IPA KELAS IV - Ni KomangAyu Sutami (Indonesian Journal Of Educational Research and Review, 2018)
The purpose of this research is to determine the significant differences of mastering science knowledge competence between class that are taught by cooperative learning model type student facilitator and explaining based reinforcement and class that are taught by conventional learning in grade IV students in SD Gugus Budi Utomo East Denpasar in academic years 2017/2018. This research is a quasi eksperimental research with non-equivalent control group design. The research subject is the IV grade of SD Gugus Budi Utomo amounting 315 student. This researh consists of 2 classes of 66 students is taken by random sampling technique. The data were collected using the test method in the form of a standard multiple choice objective test. The data obtained were analyzed using descriptive statistics and inferential statistics that t-test. Based on data analysis result obtained  thitung = 5,540 > ttabel = 2,000 at 5% significance  level and dk = 64. So Ho rejected which means  there is a significant differences of mastering science knowledge competence between class that are taught by cooperative learning model type student facilitator and explaining based reinforcement and class that are taught by conventional learning. The mean of experimental class is 86,90 and the control class is 77,36. Thus it can be concluded that the cooperative learning  model type student facilitator and explaining based reinforcement  influence on the mastery competence of science’s knowledge of grade IV students in SD Gugus Budi Utomo East Denpasar in academic years 2017/2018.